The cradle of Sarawak’s oil industry and the Canadian ‘foreign drillers’ - Justin Dit, Terry (Curtin Malaysia, 2024)
Miri is the second-largest city in Sarawak and has been recognised as home of the Malaysian oil and gas industry for well over a century. Oil was first struck on 10 October 1910 and Canada Hill, where the first well was located overlooking the small settlement at the time, was reportedly named in honour of a certain Mr. McAlpine, a Canadian employee of the Anglo-Saxon Petroleum Company who was the field manager in charge of the drilling. It is also speculated that the hill’s name was attributed to the team of Canadian drillers working in the local oil industry in the early days of Miri. Either way, the name stuck and that is how this prominent limestone ridge and famous Miri landmark obtained its name. In this article, Curtin Malaysia Borneo Studies lecturer Terry Justin Dit tells of the inimitable Canadian oil drillers who brought their expertise and skills in oil extraction and left their mark on Miri with the now famous Canada Hill overlooking Miri city named in their honour. He also relates how the knowledge and skills the locals gained from these early pioneers and later generations of oil and gas professionals resulted in Sarawak exporting its own expertise in the field to other parts of the world